Spatio-Temporal Structure of MHD Pulses with Magnetosphere: Understanding the similarities and differences in MHD oscillatory processes in solar and space plasmas (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Magneto hydrodynamic (MHD) oscillatory procedures in various plasma systems, for example, the crown of the Sun and the Earth's magnetosphere show fascinating similitude’s and contrasts, which so far got little consideration and stay under-abused. The effective authorizing inside the previous ten years of SDO, Hinode, STEREO and THEMIS shuttle, in mix with developed investigation of information from prior rocket (Wind, SOHO, ACE, Cluster, TRACE and RHESSI) makes it convenient to study the expansiveness of perceptions giving proof for MHD oscillatory master cesses in solar and space plasmas, and cutting edge hypothetical displaying